Compressive Strength of Bulk-Fill and Conventional Nano-hybrid Composite Resins: An in Vitro Study - Mofidi, Maryam; Zanguei, Elham; Shadman, Niloofar; Salehi, Hamed (Journal of Dental School, 2021)
Objectives Evaluation of the properties of recently introduced bulk-fill composite resins from different aspects is important. We aimed to evaluate the compressive strength of two bulk-fill composite resins with different viscosities compared with one conventional composite resin. Methods This in vitro study evaluated two different bulk-fill composite resins and one conventional composite resin. Twelve samples were prepared for each group in a mold, measuring 4 mm in diameter and 6 mm in height. In group 1, x-tra fil bulk-fill composite resin was light-cured with 4-mm thickness for 40 seconds. Then, a 2-mm thick increment of composite resin from the same brand was placed over it and light-cured. In group 2, x-tra base composite resin was light-cured with 4 mm thickness. Then, Grandio conventional composite resin was placed over it with 2-mm thickness and light-cured. In group 3, Grandio conventional composite resin was placed in 2-mm thickness using the incremental technique and light-cured. The samples were stored in distilled water at 37°C for 48 hours, followed by the compressive strength test in a universal testing machine at a crosshead speed of 1 mm/minute. The data were analyzed with SPSS 21 using one-way ANOVA and post hoc Tukey’s test. Statistical significance was set at P<0.05. Results There were no significant differences in compressive strength values of the three study groups (P>0.05). Conclusion The bulk-fill composite resins evaluated in the present study exhibited compressive strength values similar to that of the conventional composite resin, indicating favorable compressive strength, with decreased working time.